A technique for the processing of multidimensional data of microscopic images of endocrine cancers - M. V. Sprindzuk; L. M. Lynkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Practical technique for processing of multi-dimensional data using the example of image texture data obtained from microscopic ovarian cancer images is described.